THE EFFECT OF GREEN STRATEGY AND GREEN INVESTMENT TOWARD CARBON EMISSION DISCLOSURE - Zalida Afni; Lindawati Gani; Chaerul D Djakman; Elvia Sauki (Fakultas Pendidikan Ekonomi dan Bisnis, 2018)
This research aims to test the influence of the green strategy and green investment against disclosure of carbon emissions. Global warming leads to extreme climate change in various places around the world including in Indonesia. There is strong evidence that it is caused by human activity, mainly from burning fossil fuels so as to have an impact on the increasing greenhouse gases. One of the company's efforts in reducing the impact of carbon emissions is by disclosure of carbon emissions. Research on the relationship of the disclosure of carbon emissions by a factor of green strategy and green investments at private sector organization is still relatively limited and there are differences in the methods used. This research contributes to providing empirical evidence about the influence of the green strategy and green investment against disclosure of carbon emissions. Research on the relationship of the disclosure of carbon emissions by a factor of green strategy and green investments at private sector organization is still relatively limited and there are differences in the methods used. This research contributes to providing empirical evidence about the influence of the green strategy and green investment against disclosure of carbon emissions. This research using a sample of companies listed on stock exchanges in the country which is included in the rate of carbon emissions in the world, namely Indonesia and German. This study uses data from the 2014-2016 period in the annual report and the corporate sustainability report. The results showed that there is a significant influence of the green strategy and green investment against disclosure of carbon emissions